State estimation in a smart distribution system. Issue 1 (2nd January 2017) - Liu, Min
ABSTRACT: State estimation (SE) is a key enabler for any number of "smart grid" applications on the distribution system. Based on the weighted least square (WLS) approach, this paper proposed a state estimator considering different measurements among which are voltage magnitude, voltage phase-angle, branch current magnitude, branch current phase angle, load current magnitude, load current phase angle, real power flow, reactive power flow, real power and reactive power. Based on the analysis of the measurements provided by the advanced metering instrument (AMI) and phasor measurement unit (PMU), the effects of installing AMI and PMU on the estimation accuracy of SE are simulated and analysed. Simulation results indicated that (1) by taking PMU measurements into consideration, the estimation error of both voltage magnitude and angle can be greatly reduced and the optimal measurement portfolio of PMUs is the combination of voltage magnitude, voltage angle, load current magnitude and load current angle; and (2) if AMI has the same measurement accuracy as PMUs, it can reduce the estimation error of voltage magnitude obviously like PMUs but has little effect on the estimation error of voltage angle.